The History of Nursing Research Methodology in Iran: A Mixed Methods Study - Adib-Hajbaghery, Mohsen; Rezaei-Gazki, Parvin; mazhariazad, fereshteh; Raddadi, Yasaman (Advances in Nursing & Midwifery, 2021)
Introduction: Nursing research has dramatic effects on nursing practice. Studying the history of nursing research can provide valuable information about past challenges and future prospects. This study aimed to explore the history of nursing research methodology in Iran. Methods: This was a mixed methods study. In the quantitative part, articles published by nurses in the last four decades were reviewed using a checklist. In the qualitative part, several Iranian nursing doyens and experts were recruited through purposeful and snowball sampling and interviewed through semi-structured interviews. The main focus of the interviews was on the history of nursing research methodology in Iran. Qualitative data were analyzed through conventional content analysis. Finally, the findings of the two parts were merged. Results: The number of nursing articles and journals increased from 39 and one in the 1980s to respectively 461 and thirty in the 2010s. Articles published in the 1980s and the 1990s were mainly related to descriptive researches (91.9% and 88.4%, respectively), while articles in the 2000s were mainly related to quasi-experimental researches (42.8%) and articles in the 2000s were mainly related to quasi-experimental and experimental researches. Qualitative researches become common in the 2010s. The results of the qualitative part were presented based on three era. Conclusions: Nursing research in Iran has had significant improvements in the last three era. Yet, nurses need to make more serious attempts to provide conclusive evidence for nursing practice, improve the Iranians’ health status, and promote the position of nursing in Iran and the position of Iranian nursing in the world.